Information seeking with selective memory (2018)
Prospective recollections share common features; for instance, information that is recalled tends to be congruent, recent or pleasant. Memory is a one-sided archivist. This paper examines how asymmetrical recall rates shape decisions to search for information. I propose a signaling bandit model, where selective recall makes one signal more likely to be remembered than another. Forgetting makes information that has never been known indistinguishable from information which has been forgotten. The ambivalence of "absent signals" sustains opposing ways by which oblivion shapes information search. Information becomes less valuable inasmuch as telling signals are systematically eliminated. Yet the one-sided elimination of signals also makes the absence of memories informative. And while the first logic derives in under-experimentation, the second one justifies over-experimentation.